2012
DOI: 10.1016/j.juro.2011.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Symptoms of Anterior Urethral Stricture Disease: A Disease Specific, Patient Reported Questionnaire to Measure Outcomes

Abstract: While the American Urological Association symptom index captures the most common voiding complaints of men with urethral stricture, 21% of those who presented for urethroplasty did not have voiding symptoms assessed by the index. A validated, disease specific instrument is needed to fully capture the presenting voiding symptoms and sexual dysfunction complaints of men with urethral stricture disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…It demonstrates the importance of evaluating HRQoL even in patients undergoing USS and stands in contrast to other studies assessing functional related QoL only [8,28,29].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…It demonstrates the importance of evaluating HRQoL even in patients undergoing USS and stands in contrast to other studies assessing functional related QoL only [8,28,29].…”
Section: Discussionmentioning
confidence: 78%
“…Assessing, reporting and comparing these outcome measures clearly aim to improve quality of care and reduce costs [6][7][8]. If physicians make treatment decisions based on health outcomes, medical errors and unnecessary treatments could be prevented; thus, patients are more likely to receive high-quality care [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Three articles used the AUA-SS instrument, which was originally developed for men with benign prostatic hyperplasia, 5-7 and the other article contained an instrument that was developed specifically for men with anterior urethral strictures. 8 The LUTS instrument was used in a different manner for each of the 4 studies.…”
Section: Studies On Luts Instrumentsmentioning
confidence: 99%
“…5 They concluded that the AUA-SS has a floor effect in that approximately 21% of preoperative LUTS related to a known anterior urethral stricture was not captured. In 2011 Jackson et al published the only anterior urethroplasty specific instrument.…”
Section: Studies On Luts Instrumentsmentioning
confidence: 99%